2022
DOI: 10.1038/s41598-022-07452-5
|View full text |Cite
|
Sign up to set email alerts
|

The symptom discounting effect: what to do when negative genetic test results become risk factors for alcohol use disorder

Abstract: Most consumers of genetic testing for health conditions test negative, yet the psychological perils of this are hardly known. In three experiments (N = 2103) participants discounted repercussions of alcohol use disorder (AUD), after learning or imagining that they were not genetically predisposed to AUD. Such discounting can lead people to avoid treatment and to feel safe to continue or even increase their drinking, ironically turning the negative genetic feedback into a risk factor for AUD. Concerningly, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a recent study (Ahn & Perricone, 2022), we empirically examined false reassurance using AUD as a target condition. The type of reassurance we tested was not just the type that can be considered justifiable.…”
Section: Effects Of Learning That One Does Not Have An Increased Gene...mentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study (Ahn & Perricone, 2022), we empirically examined false reassurance using AUD as a target condition. The type of reassurance we tested was not just the type that can be considered justifiable.…”
Section: Effects Of Learning That One Does Not Have An Increased Gene...mentioning
confidence: 99%
“…We also tested the effectiveness of the debriefing process currently used by 23andMe, which was designed to prevent false reassurance by emphasizing that environmental factors and genetic factors not examined in the test could still put someone at risk. Results were concerning, as we found that these materials were ineffective for those individuals who reported already engaging in problematic drinking behaviors (Ahn & Perricone, 2022). To address this problem, we developed additional educational materials emphasizing that once the symptoms of AUD are present, their ramifications should be taken as equally risky whether or not these symptoms were caused by genes (as formalized as the causal Markov condition; see Pearl, 1988, and Fig.…”
Section: Effects Of Learning That One Does Not Have An Increased Gene...mentioning
confidence: 99%
See 2 more Smart Citations